Penerapan Terapi Nonfarmakologis pada Nyeri Persalinan : Application of Nonpharmacological Therapy for Labor Pain - Prabandari, Fitria; Sofiana, Juni; Sumarni; Rosmawati (Universitas Ngudi waluyo, 2023)
Labor pain is a manifestation of contractions which are caused by the shortening of the uterine muscles and cause pain in the waist, abdominal area and radiate towards the thighs and cause the cervix to open. With this opening of the cervix, labor will occur. The severity of the pain is exacerbated by anxiety, tension and fear. Failure to deal with labor pain can increase anxiety and even make labor abnormal. Non-pharmacological therapy can be an alternative to reduce labor pain apart from using pharmacological therapy. Midwives as birth attendants apply non-pharmacological therapy to mothers giving birth with various therapy options according to their expertise and competence. Although in Indonesia there is no law that specifically regulates the implementation of complementary midwifery services, the provision of complementary medicine in general has been regulated in Minister of Health Decree No. 1109/Menkes/Per/IX/2007 concerning complementary-alternative medicine. The aim of this research is to determine the frequency of application of non-pharmacological therapy for labor pain applied by Midwives in Hospitals, Community Health Centers, and Midwives' Independent Practice. Non-pharmacological therapy in this research includes: massage and touch, maternal movement and position, breathing and relaxation techniques, application cold or hot, music or audio analgesics, aromatherapy, birthball method, acupuncture, acupressure, yoga, and hypnosis. using the survey method, the sample was 150 respondents. The survey results showed that the majority of respondents were > 35 years old (71.3%), had been practicing midwifery for > 10 years (59.3%), and the majority of respondents worked in community health centers (64.7%), applying non-pharmacological therapy. Most of the respondents used breathing and relaxation techniques (38.7%). Advice for midwives is that midwives should also study and apply non-pharmacological therapy which is still rarely used as an alternative measure to reduce labor pain. Abstrak Nyeri persalinan merupakan manifestasi dari adanya kontraksi yang diakibatkan oleh adanya pemendekan otot rahim dan menimbulkan rasa sakit pada pinggang, daerah perut dan menjalar ke arah paha dan menyebabkan adanya pembukaan serviks, dengan adanya pembukaan servik ini maka akan terjadi persalinan. Tingkat keparahan nyeri diperburuk oleh kecemasan, ketegangan dan ketakutan. Kegagalan dalam mengatasi nyeri persalinan dapat meningkatkan kecemasan bahkan persalinan menjadi tidak normal. Terapi nonfarmakologis dapat menjadi alternatif untuk mengurangi nyeri persalinan selain menggunakan terapi farmakologis. Bidan sebagai penolong persalinan menerapkan terapi nonfarmakologis pada ibu bersalin dengan berbagai pilihan terapi sesuai dengan keahlian dan kompetensinya. Meskipun di Indonesia belum ada undang-undang yang mengatur secara khusus tentang pelaksanaan pelayanan kebidanan komplementer, namun penyelengaraan pengobatan komplementer secara umum telah diatur dalam Kepmenkes No. 1109/Menkes/Per/IX/2007 tentang pengobatan komplementer-alternatif. Tujuan penelitian ini adalah mengetahui frekuensi penerapan terapi nonfarmakologi pada nyeri persalinan yang diterapkan oleh Bidan di Rumah Sakit, Puskesmas, dan Praktik Mandiri Bidan, terapi nonfarmakologis dalam penelitian ini antara lain: masase dan sentuhan, pergerakan dan posisi maternal, teknik pernafasan dan relaksasi, aplikasi dingin atau panas, music atau audioanalgesik, aromatherapy, metode birthball, akupuntur, acupressure, yoga, dan hypnosis. menggunakan metode survey, sampel sebesar 150 responden. Hasil survey menunjukkan bahwa sebagian besar responden berusia > 35 tahun (71,3%), telah melakukan praktik kebidanan > 10 tahun (59,3%), dan sebagian besar responden bekerja di Puskesmas (64,7%), penerapan terapi nonfarmakologi yang dilakukan responden sebagian besar adalah teknik pernafasan dan relaksasi (38,7%). Saran bagi Bidan sebaiknya Bidan juga mempelajari dan menerapkan terapi nonfarmakologi yang masih jarang dilakukan sebagai alternatif tindakan menurunkan nyeri persalinan.